PERAN DAKWAH DALAM MEMPERBAIKI MASYARAKAT BUGHOT - Candra Darmawan (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2015)
Da’wah is a sacred duty and lasting for all Muslims. With propaganda, Islam can spread and take root to all corners of the region . So the fruit of propaganda can we see and feel in the midst of society. Among these propaganda was instrumental in fostering and developing the major communities in accordance with the ideals of Islam that rahmatan lil - 'alamin .